QED effects induced harmonics generation in extreme intense laser foil interaction. (28th February 2018) - Yu, J Y; Yuan, T; Liu, W Y; Chen, M; Luo, W; Weng, S M; Sheng, Z M
Abstract: A new mechanism of harmonics generation (HG) induced by quantum electrodynamics (QED) effects in extreme intense laser foil interaction is found and investigated by particle-in-cell (PIC) simulations. When two laser pulses with identical intensities of 1.6 × 10 24 W cm − 2 are counter-incident on a thin foil target, harmonics emission is observed in their reflected electromagnetic waves. Such harmonics radiation is excited due to transversely oscillating electric currents coming from the vibration of QED effect generated e − e + pairs. The effects of laser intensity and polarization were studied. By distinguishing the cascade depth of generated photons and pairs, the influence of QED cascades on HG was analyzed. Although the current HG is not an efficient way for radiation source applications, it may provide a unique way to detect the QED processes in the near future ultra-relativistic laser solid interactions.